Remote sensing for biodiversity and wildlife management : synthesis and applications - Franklin, Steven E. (McGraw-Hill's AccessEngineering., 2012)
"Practical applications of remote sensing technology in wildlife management. This comprehensive guide provides fundamental information as well as practical applications of remote sensing technology in the wildlife management environment. Pioneering global case studies and illustrative examples are included. The book will be of great interest to both environmental engineers specializing in sustainability and to spatial information specialists such as remote sensing scientists, mapping practitioners, and GIS specialists.".